TO THE QUESTION OF PRE-TRIAL ADJUSTING OF THE CONFLICTS IN THE MODERN LEGAL SYSTEM OF THE REPUBLIC OF KAZAKHSTAN - Ayupova, Z.K.; Kussainov, D.U.; Nagan, Winston (Academic Journal of Physical and Chemical Sciences, 2018)
The judicial system belongs to the branch of power, which, being the original generator of all Kazakhstan transformations, would be able to transform Kazakhstan in really civilized, law-abiding state. The accrued democratic society and legal state will demand complete reformation of all system of justice, not only courts, but also other law-enforcement institutes of state power. Thus, after acquisition of independence, all this time of reforms, development of the independent judicial system, and realization of judicial and legal reform. Realization of political and economic transformations entailed and deep reformation of legal sphere of the society, legal reform by itself, had to move in accordance with the realization of political and economic transformations. The governmental program of the legal reform assisted to the legal system in Kazakhstan, according to the world standards and future realization.